Legal Implications of Differences in Goods Price Labels in Shop Cashier Showcases for Entrepreneurs - Suci Laboro; Nurul Fazri Elfikri (Estudiante Law Journal, 2022)
The purpose of this research is to know and analyze about iThe legal implication is that there is a difference in the price tag of goods on the window display and the shop cashier for entrepreneurs, which has implications for the provisions of the Consumer Protection Act and Permendag No. 35 of 2013 which can result in criminal sanctions and administrative sanctions as well as payment based on the lowest price tag. Based on the aspect of responsibility as a business actor, namely public accountability and private responsibility, it has implications for law enforcement (criminal sanctions and administrative sanctions). The problem of price differences in shop windows and during the payment process at the cashier also has implications for the course of the buying and selling process in social life, among other things, has implications for price uncertainty, injustice for consumers, and has implications for benefits that only benefit business actors...